You Have Control: aviation communication application for safety-critical times in surgery. Issue 9 (November 2020) - Hardie, J.A.; Oeppen, R.S.; Shaw, G.; Holden, C.; Tayler, N.; Brennan, P.A.
Abstract: High-risk organisations (HRO), including aviation, undergo formal communication training, with emphasis on safety-critical moments. Such training is not widespread or mandatory in healthcare, and while there are many differences both share the 'human element' with circumstances leading to an increased risk of harm. A typical operating theatre consists of an operating surgeon, and an assisting surgeon, roles that may change throughout the course of a procedure. Similarly, a training aircraft or multi-crew cockpit (flight deck) has a pilot in control, or 'pilot flying', and a 'pilot not flying'. Both interact with wider teams, for example the scrub team and air traffic controllers, respectively. Surgical error is the second most prevalent cause of preventable harm to patients after drug errors. Every year in the UK National Health Service (NHS), there are typically 500 never events, 21, 000 serious incidents, and many more episodes of physical or psychological harm. Ineffective communication (46%) is the most common behavioural factor leading to a never event. In this review, we examine the concept of 'sterile cockpit', use of unambiguous terminology, callsigns, important information readback, sharing of mental models, and the mini-brief, and how these may be used to reduce patient harm during safety-critical moments.